Mapping the History of Journalism & Mass Communication Educator: 30 Years of Publication (1990–2019). (December 2020) - Gearhart, Sherice; Cho, Janice
University educators and administrators have used Journalism & Mass Communication Educator as an outlet to share ideas. As the journal enters its 75th year of publication, it is also decades into the transition to peer review. Thus, it is important to review publication trends since this development. This study analyzes 30 years of research articles printed from 1990 to 2019. Aspects of article authorship are examined and reveal trends in the publication history. Results demonstrate the growing amount of diversity across a number of aspects and remains on par with publication trends throughout the discipline.